2018
DOI: 10.1111/clr.13386
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of single crowns supported by short, moderately rough implants—A prospective 10‐year cohort study

Abstract: Objectives To evaluate prospectively the clinical and radiographic outcomes after ten years of short (6 mm) implants with a moderately rough surface supporting single crowns in the posterior region. Material and Methods Forty 6 mm modified sandblasted large‐grit acid‐etched (mod‐SLA), soft tissue level implants were installed in the distal segments of 35 consecutive patients. After 6 weeks of healing, abutments were tightened, and single porcelain‐fused‐to‐metal crowns were cemented. Implant survival, marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 28 publications
(65 reference statements)
10
62
6
Order By: Relevance
“…The 10-year survival rate of SLA Ti implants was reported to be higher than 95%, even in periodontally compromised patients, although strict periodontal interventions were applied to these patients [20]. Similar results were found in 10-year prospective studies investigating the survival rates of dental implants with SLA surfaces [19,21,22]. This modified surface, roughened at the micro-scale, is one of the dental implant surfaces that has been most frequently tested in clinics for the longest period.…”
Section: Sandblasted Large-grit Acid-etched (Sla) Surfacesupporting
confidence: 64%
See 1 more Smart Citation
“…The 10-year survival rate of SLA Ti implants was reported to be higher than 95%, even in periodontally compromised patients, although strict periodontal interventions were applied to these patients [20]. Similar results were found in 10-year prospective studies investigating the survival rates of dental implants with SLA surfaces [19,21,22]. This modified surface, roughened at the micro-scale, is one of the dental implant surfaces that has been most frequently tested in clinics for the longest period.…”
Section: Sandblasted Large-grit Acid-etched (Sla) Surfacesupporting
confidence: 64%
“…Regardless of whether an SLA surface is hydrophobic or hydrophilic, this dental implant surface has shown excellent long-term clinical results [18][19][20][21][22]. A previous 10-year retrospective study investigating more than 500 SLA Ti implants concluded that both the survival and success rates were 97% or higher [18].…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…The European population is getting older, with an increasing concern about oral health: according to Schimmel et al., implant‐prosthetic rehabilitation has become routine practice in elderly patients, with well‐documented long‐term survival rates (>10 years) . Nevertheless, coexisting systemic risk factors should carefully be taken into account by clinicians and implant success could be affected by either mechanical or biological complications .…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent clinical studies have proven high survival rates of short implants that were comparable to the survival rates of standard implants. 6,7 Our previous study demonstrated that the 2-year performance of 6.5-mm short implants placed using osteotome sinus floor elevation procedures, exhibited similar clinical outcomes to long implants placed using lateral sinus floor elevation in severely atrophic posterior maxillae. 8 However, there is limited evidence for short implants from studies with larger sample sizes and longer follow-up.…”
Section: Introductionmentioning
confidence: 93%